2020
DOI: 10.1111/tpj.14891
|View full text |Cite
|
Sign up to set email alerts
|

The fungal NADPH oxidase is an essential element for the molecular dialog between Trichoderma and Arabidopsis

Abstract: SUMMARY Members of the fungal genus Trichoderma stimulate growth and reinforce plant immunity. Nevertheless, how fungal signaling elements mediate the establishment of a successful Trichoderma−plant interaction is largely unknown. In this work, we analyzed growth, root architecture and defense in an Arabidopsis−Trichoderma co‐cultivation system, including the wild‐type (WT) strain of the fungus and mutants affected in NADPH oxidase. Global gene expression profiles were assessed in both the plant and the fungus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 71 publications
1
12
0
Order By: Relevance
“…Considering the NADPH oxidase domain of PCA1, a relevance of an NADPH oxidase involved in ROS production for plant-fungus interaction was previously shown for T. atroviride [82]. For F. oxysporum , NADPH oxidase was found to be essential for chemotropic response to the presence of a plant [33].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the NADPH oxidase domain of PCA1, a relevance of an NADPH oxidase involved in ROS production for plant-fungus interaction was previously shown for T. atroviride [82]. For F. oxysporum , NADPH oxidase was found to be essential for chemotropic response to the presence of a plant [33].…”
Section: Discussionmentioning
confidence: 99%
“…liquidambaris ‐enhanced oxidative signals of rice are highly conditional upon particular environmental conditions, for example, the amount of soil N availability. Although plant oxidative signals are generally produced at the early stages after microbe infection (Jedelská et al, 2021; Villalobos‐Escobedo et al, 2020), these signals could also be induced in host plantlets at a later stage by fungal endophytes (Cui et al, 2017). In the present study, Ph.…”
Section: Discussionmentioning
confidence: 99%
“…atroviride has an intracellular invertase (Triat51014) and two putative sucrose transporters (Triat226844 and Triat83012) to be able to use plant‐derived carbon. Recently, Villalobos‐Escobedo et al (2020) demonstrated that T . atroviride represses its genes encoding enzymes involved in complex carbohydrate degradation prior to root colonization of Arabidopsis , suggesting that its saprophytic behaviour changes to acquire and use the simple sugars available in root exudates.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Trichoderma includes opportunistic avirulent fungal species with a versatile lifestyle, which rely on plant‐derived sugars for fast growth and root colonization. They also thrive as decomposers of decaying plant residues or parasitize other fungi when nutrients are limiting (Ramírez‐Valdespino, Casas‐Flores, & Olmedo‐Monfil, 2019; Vargas, Crutcher, & Kenerley, 2011; Vargas, Mandawe, & Kenerley, 2009; Villalobos‐Escobedo et al, 2020). Upon root colonization, Trichoderma influences shoot performance through long distance, systemic signalling relying on oxylipins that strengthen photosynthesis, sugar homeostasis and exudation patterns (Coppola et al, 2019; Doni et al, 2019; Macías‐Rodríguez, Guzmán‐Gómez, García‐Juárez, & Contreras‐Cornejo, 2018; Wang, Borrego, Kenerley, & Kolomiets, 2020).…”
Section: Introductionmentioning
confidence: 99%